Development of Higher Education in Kazakhstan: from Centralization Control to Institutional Autonomy (Journal of Educational Sciences, 2017)
In this article authors want to pay attention to features of a new stage of development of system of the higher education – transition of higher education institutions to the mode of institutional autonomy. In article the historical overview is carried out and stages of decentralization of system of the higher education are allocated: 1 stage (early 20th century-1990) – a stage of centralized management of education; the 2nd stage (1991 – 1998) – reforming of system of the higher education, formation of the legislative and regulatory base of transition to decentralization, privatization of higher education institutions; 3rd stage (1999 – 2010) – decentralization of management and financing of the higher education of RK; the 4th stage (2011 – till present) – implementation of system of autonomous organizations of education, provision of institutional autonomy to higher education institutions. Characterizing the last stage, authors of article carried out primary analysis of development of forms of institutional autonomy in the higher education institutions of Kazakhstan.It is known the foundation of the development of the national higher education system is the resolution of this question because since 2015 it is granted autonomy to national research universities, since 2016 – to the national higher educational institutions, and since 2018 – to the rest of the higher education institutions. We want to note that process of decentralization of the higher education already began from the first days of acquisition of independence, the functioning of higher education institution as autonomous organization is a logical conclusion of this process.Key words: higher education, autonomy, university, the management of the University.